Media Kotak Misteri Untuk Meningkatkan Kemampuan Kognitif Anak TK - Ulfatun Ni'mah; Syamsiah D Syamsiah D; Andi Mardiana (Universitas Negeri Makassar, 2022)
The researcher aims to improve children's cognitive abilities before and after the mystery box media is applied and to determine whether there is an influence of mystery box media on the skills of group B children of Dharma Wanita Tenggong Kindergarten, Rejotangan District, Tulungagung Regency. By using a quantitative approach with a Quasi Experiment Design type of research. The subjects in this study were group B at Dharma Wanita Tenggong Kindergarten, Rejotangan District, Tulungagung Regency, which consisted of 15 children consisting of 6 boys and nine girls. Based on the results of the application of mystery box media in the first cycle, children's cognitive abilities reached 67%. The use of mystery box media continued in the second cycle; children's cognitive skills got 93%, meaning that there was an influence of mystery box media variables on the cognitive abilities of group B children in Dharma Wanita Tenggong Kindergarten. Rejotangan District, Tulungagung Regency.